Rancangbangun Alat Press Baglog Jamur Dua Silinder Dengan Penggerak Motor Listrik - Fajri Husna; Fiqi Al Hidayat; Muqorrobin Muqorrobin; Yose Sebastian; Meinilwita Yulia (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Mushrooms are plants that have a nucleus, spores, no chlorophyll and are heterotrophic. Mushrooms can not produce their own food, they get nutrition by way of absorption. Nutrients are absorbed from the mushrooms existing in the organic material in which they live (Alexopoulos and Mims, 1996). Baglog is a media into the growth of mushrooms which comprises a mixture of basic materials such as wood sawdust, rice bran, limestone and so on. The mixture will be allowed to stand for 2-3 days so that all the materials decompose properly. All the material that has decomposed properly inserted into the plastic which will then be compacted. This media must be completely solid to support the growth of mushrooms. Compaction is done by using a press baglog mushrooms (Sunarmi and Saparinto, 2010).Â Keywords: mushroom baglog, two cylinder, electric motor